The impact of social media in travel decision-making process among the Y and Z generations of music festivals in Vojvodina and Hungary - Süli, Dorottya; Martyin-Csamangó, Zita (Turizam, 2020)
As a remarkable trend, social media is becoming a primary source of information and impressions about tourism destinations. Travellers, especially the young generations are using intensively the information from the web in their decisions and they have widely adopted social media in order to search for advice, share and annotate their experiences. The recent shift towards more visual content can even more strongly affect others' consumption habits, (touristic) decisions, image and opinions on different places and events. Knowing about travelling habits and decision-making processes of young generations can be useful for the tourism service suppliers, because their habits can substantially affect the future tourism development directions. The aim of this study was to analyze the role and importance of social media usage in travel decision-making among the young participants of music festivals in Vojvodina and Hungary. On the one hand we made a questionnaire survey among the participants of two festivals from the Y and Z generations in the study area (in Green Future of Ada and in the Youth Days of Szeged), and among the students from the University of Szeged, who usually visit festivals. As social media can indirectly contribute to the promotion of festivals and settlements through the public posts of the festivals, on the other hand we analyzed the posts of the selected music festivals on a photo-sharing site (Instagram), searching the hashtags which refer to the places of the festivals. Based on the results it can be concluded that young people’s travel and festival decisions are considerably influenced by the social media, so the role of online marketing can be significant to reach these generations. Therefore, the shared social media content linked to festivals can make some places better known by shaping their image. With the improved image these posts can contribute to attract more tourists.Keywords: social media, Y and Z generations, tourists’ decisions, festival tourism, destination image